Constitucionalismo da austeridade, momentos desconstituintes e as emendas constitucionais acerca do novo regime fiscal da União - Marisa Neves Magalhães Cordeiro (2023)
Largely based on a critical view of the social constitutionalism, recent amendments to the 1988 Brazilian Federal Constitution have constrained public expenses, leading to human rights violations. Such movement endorses the regressive and selective aspects of the economic policies traditionally conducted in Brazil. In that sense, the present study aims to assess the constitutional changes to the Federal Fiscal Regime, which was installed by the Constitutional Amendment n° 95/2016. This amendment established a public spending cap at the federal level based on a budget freeze for primary expenses with annual spending growth tied to the inflation rate of the prior year. Accordingly, the main objective of the exploratory research is to answer the following question: have the constitutional changes implemented since the Amendment n° 95 continued to dismantle the Brazilian constitutional project of building an inclusive and plural society? Or do these amendments actually tackle the budget freeze and therefore reestablish the constitutional social protection network? In view of these methodological questions, the study will bear a deductive reasoning and will be based mainly on Brazilian literature on constitutional law, aiming to provide for a critical analysis regarding the selected constitutional amendments. Additionally, aiming to deepen the studies concerning the phenomenon of “austerity constitutionalism”, some of the intersections between constitutional law, financial law, economic law and public finances will be invoked, mainly from a substantial perspective.